LEARNING STYLES OF CHINESE AS A SECOND FOREIGN LANGUAGE: A CASE OF ENGLISH-MAJORED STUDENTS AT BANKING UNIVERSITY OF HO CHI MINH CITY - Vu, Luu Hon (VNU Journal of Foreign Studies; Vol 37 No 2DO - 10.25073/2525-2445/vnufs.4710, 2021)
This article studies the learning styles of Chinese as a second foreign language of English-majored students at Banking University of Ho Chi Minh City. Based on Reid’s learning style theory (1984), we conducted a questionnaire survey with 205 students. The results show that students’ learning styles all belong to the main learning styles, in which students prefer the auditory learning style. Gender, time spent studying Chinese and regions do not affect students’ learning styles. Students of younger ages will prefer the auditory learning style. The more students are inclined to kinesthetic type of learning, the higher their academic performance will be.